Authority of the Notary in Making Murabahah Deeds (American Journal of Society and Law, 2023)
The background of this research is that there are notaries who still make sharia contracts without paying attention to or in accordance with sharia principles, especially for non-Muslim notaries. The purpose of this study is to provide an understanding of the authority of a notary in making a murabaha contract deed in Islamic banks. This research, which uses normative legal research methods with a statute legal approach and conceptual approach, resulted in the following findings: first, with regard to the legal requirements of the agreement in making a murabaha contract deed by taking into account sharia principles; and second, with regard to the professional code of ethics of a notary.